Communication, Affect, & Learning in the Classroom - Wrench, Jason S.; Richmond, Virginia Peck; Gorham, Joan (Open textbook library., 2020)
Communication, Affect, & Learning in the Classroom was original published by Virginia Richmond and Joan Gorham in 1992 and then updated a decade later by Virginia Richmond, Jason S. Wrench, and Joan Gorham in 2001. As we enter into the revision of the 3rd edition of the text, the basic content has not been drastically altered over the years. However, the research in Instructional Communication has clearly become more prominent and stronger. Probably the single most important development in the past two decades was the publication of the Handbook of Instructional Communication: Rhetorical and Relational Perspectives edited by Mottet et al. (2006). The purpose of the handbook was to synthesize the first three decades of research in instructional communication into a single volume that could help both researchers and instructors understand the value of communication in the instructional process.